Answer:
The correct answer will be:
![-\dfrac{62}{23}](https://tex.z-dn.net/?f=-%5Cdfrac%7B62%7D%7B23%7D)
Step-by-step explanation:
It is given that :
Initial temperature, ![T_1 = 0^\circ F](https://tex.z-dn.net/?f=T_1%20%3D%200%5E%5Ccirc%20F)
Final temperature,
![T_2 = -15\dfrac{1}{2}^\circ F\\\Rightarrow T_2 = -\dfrac{15\times 2+1}{2} ^\circ F\\\Rightarrow T_2 = -\dfrac{31}{2} ^\circ F](https://tex.z-dn.net/?f=T_2%20%3D%20-15%5Cdfrac%7B1%7D%7B2%7D%5E%5Ccirc%20F%5C%5C%5CRightarrow%20T_2%20%3D%20-%5Cdfrac%7B15%5Ctimes%202%2B1%7D%7B2%7D%20%5E%5Ccirc%20F%5C%5C%5CRightarrow%20T_2%20%3D%20-%5Cdfrac%7B31%7D%7B2%7D%20%5E%5Ccirc%20F)
Time taken :
![5\dfrac{3}{4}\ hrs = \dfrac{5 \times 4+3}{4}\ hrs = \dfrac{23}{4}\ hrs](https://tex.z-dn.net/?f=5%5Cdfrac%7B3%7D%7B4%7D%5C%20hrs%20%3D%20%5Cdfrac%7B5%20%5Ctimes%204%2B3%7D%7B4%7D%5C%20hrs%20%3D%20%5Cdfrac%7B23%7D%7B4%7D%5C%20hrs)
Change in temperature per hour:
![\dfrac{\text{Difference of temperature}}{\text{Total Time Taken}}\\\Rightarrow \dfrac{T_2-T_1}{\text{Total Time Taken}}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Ctext%7BDifference%20of%20temperature%7D%7D%7B%5Ctext%7BTotal%20Time%20Taken%7D%7D%5C%5C%5CRightarrow%20%5Cdfrac%7BT_2-T_1%7D%7B%5Ctext%7BTotal%20Time%20Taken%7D%7D)
Putting the values of temperatures and time:
![\dfrac{\dfrac{-31}{2}-0}{\dfrac{23}{4}}\\\Rightarrow \dfrac{\dfrac{-31}{2}}{\dfrac{23}{4}}\\\Rightarrow \dfrac{-31 \times 4}{2 \times 23}} \text{---- Error done by Wen at this step}\\\Rightarrow \dfrac{-31 \times 2}{23}}\\\Rightarrow \dfrac{-62}{23}}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cdfrac%7B-31%7D%7B2%7D-0%7D%7B%5Cdfrac%7B23%7D%7B4%7D%7D%5C%5C%5CRightarrow%20%5Cdfrac%7B%5Cdfrac%7B-31%7D%7B2%7D%7D%7B%5Cdfrac%7B23%7D%7B4%7D%7D%5C%5C%5CRightarrow%20%5Cdfrac%7B-31%20%5Ctimes%204%7D%7B2%20%5Ctimes%2023%7D%7D%20%5Ctext%7B----%20Error%20done%20by%20Wen%20at%20this%20step%7D%5C%5C%5CRightarrow%20%5Cdfrac%7B-31%20%5Ctimes%202%7D%7B23%7D%7D%5C%5C%5CRightarrow%20%5Cdfrac%7B-62%7D%7B23%7D%7D)
The error done by Wen was during calculating the values of fraction.
So, the correct answer is :
instead of
Step-by-step explanation:
this simply means that the sum of both short segments must be the same as the length of the whole line.
so,
x + 6 + x + 8 = 10
2x + 14 = 10
x + 7 = 5
x = 5 - 7 = -2
Answer:
x = 2 y = 3
Step-by-step explanation: